Chikungunya Virus A Growing Global Public Health Threat - Engohang-Ndong, Jean (Infectious Diseases, 2022)
The chikungunya virus (CHIKV) is an RNA virus that is transmitted to humans by Aedes mosquitos commonly found in tropical and subtropical countries. In humans, CHIKV causes an infection with symptoms strikingly like those of the dengue virus and Zika disease, both of which are also transmitted to humans by the same genus of mosquitos. This book delves into the history of the disease and the molecular characterization of the virus. It sheds light on modern diagnosis tools that allow unambiguous identification of CHIKV infection. In addition, this book addresses the epidemiology of chikungunya fever, the distribution and spread of the disease, and the promising approaches under consideration for preventing and treating the disease.